Identifying and prioritizing the factors affecting the Iranian Sports Refereeing Ethics Code - Ahdieh Sadeghi Kalani; Shirin Zardoshtian; Shahab Bahrami; Masoud Sadeghi (Universidad de Murcia, 2021)
The purpose of this research was to compile a sports refereeing ethics code in Iran. The method of the present research was mixed (qualitative and quantitative). A total of 15 experts in the field of refereeing ethics in sports were interviewed by the method of snowball sampling. The results obtained from the interview led to a valid and reliable questionnaire that was randomly distributed among the referees and assistant referees of the Iranian premier leagues of team sports (football, volleyball, handball and basketball) and individual sports (taekwondo, karate, wrestling and swimming), with a total sample of 224 people. Analysis and coding were performed using the softwares Max Kyoda, SPSS and Smart PLS. Research findings showed that 8 themes and 61 sub-themes were extracted in this field, which include the components of behavior, corruption, communication, sociocultural aspect, family, respect, legality and justice, in this order of importance. In general, paying attention to the behavioral and corruption aspects plays an important role in improving the ethical status of sports referees in Iran.